2022
DOI: 10.1075/sar.21005.eco
|View full text |Cite
|
Sign up to set email alerts
|

Developing spoken requests during UK study abroad

Abstract: The present study tracks the longitudinal pragmatic development of spoken requests by Japanese, adult learners of English during an academic year abroad, and aims to examine whether and how their requestive performance develops over time in high and low-imposition situations. Data were collected at three points of the academic year using oral, virtual role plays, and semi-structured group interviews. Data analysis examined the type and frequency of request strategies and modification devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Nevertheless, whilst SA periods hold much promise for L2 development, increasing research has suggested that sojourners' experiences are unique, and language development does not always follow a linear trajectory. A number of empirical studies (e.g., Barron 2003;Economidou-Kogetsidis and Halenko 2022;Halenko and Economidou-Kogetsidis 2022;Li 2014;Schauer 2009) revealed that there can be much variation in the amount and type of pragmatic gains learners receive during their SA sojourns, thus confirming that the relationship between SA contexts and pragmatic development is a complex one. For instance, learners who do not immerse themselves sufficiently into the L2 culture often miss valuable opportunities for interacting with fluent speakers of the target language or observing authentic interactions in the TL culture, therefore preventing them from receiving a sufficient amount of L2 input.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, whilst SA periods hold much promise for L2 development, increasing research has suggested that sojourners' experiences are unique, and language development does not always follow a linear trajectory. A number of empirical studies (e.g., Barron 2003;Economidou-Kogetsidis and Halenko 2022;Halenko and Economidou-Kogetsidis 2022;Li 2014;Schauer 2009) revealed that there can be much variation in the amount and type of pragmatic gains learners receive during their SA sojourns, thus confirming that the relationship between SA contexts and pragmatic development is a complex one. For instance, learners who do not immerse themselves sufficiently into the L2 culture often miss valuable opportunities for interacting with fluent speakers of the target language or observing authentic interactions in the TL culture, therefore preventing them from receiving a sufficient amount of L2 input.…”
Section: Introductionmentioning
confidence: 99%